An Introduction to Embodied Cognitive Phonology: Claw-5 Hand-shape Distribution in ASL and Libras - Occhino, Corrine (Complutense Journal of English Studies, 2017)
While the arbitrariness of the sign has occupied a central space in linguistic theory for a century, counter-evidence to this basic tenet has been mounting. Recent findings from cross-linguistic studies on spoken languages have suggested that, contrary to purely arbitrary distributions of phonological content, languages often exhibit systematic and regular phonological and sub-phonological patterns of form-meaning mappings. To date, studies of distributional tendencies of this kind have not been conducted for signed languages. In an investigation of phoneme distribution in American Sign Language (ASL) and Língua Brasileira de Sinais (Libras), tokens of the claw-5 handshape were extracted and analyzed for whether the handshape contributed to the overall meaning of the sign. The data suggests that distribution of the claw-5 handshape is not randomly distributed across the lexicon, but clusters around six form-meaning patterns: convex-concave, Unitary-elements, non-compact matter, hand-as-hand, touch, and interlocking. Interestingly, feature-level motivations were uncovered as the source of the mappings These findings are considered within a new cognitive framework to better understand how and why sub-morphemic units develop and maintain motivated form-meaning mappings. The model proposed here, Embodied Cognitive Phonology, builds on cognitive and usage-based approaches but incorporates theories of embodiment to address the source of the claw-5 mappings. Embodied Cognitive Phonology provides a unifying framework for understanding the perceived differences in phonological patterning and organization across the modalities. Both language-internal and language-external sources of motivation contribute to the emergence of form-meaning mappings. Arbitrariness is argued to be but one possible outcome from the process of emergence and schematization of phonological content, and exists alongside motivation as a legitimate state of linguistic units of all sizes of complexity. Importantly, because language is dynamic, these states are not fixed, but are in continuous flux, as language users reinvent and reinterpret form and meaning over time.